Personality‐obesity associations are driven by narrow traits: A meta‐analysis. (15th April 2019) - Vainik, Uku; Dagher, Alain; Realo, Anu; Colodro‐Conde, Lucía; Mortensen, Erik Lykke; Jang, Kerry; Juko, Ando; Kandler, Christian; Sørensen, Thorkild I.A.; Mõttus, René
Summary: Obesity has inconsistent associations with broad personality domains, possibly because the links pertain to only some facets of these domains. Collating published and unpublished studies (N = 14 848), we meta‐analysed the associations between body mass index (BMI) and Five‐Factor Model personality domains as well as 30 Five‐Factor Model personality facets. At the domain level, BMI had a positive association with Neuroticism and a negative association with Conscientiousness domains. At the facet level, we found associations between BMI and 15 facets from all five personality domains, with only some Neuroticism and Conscientiousness facets among them. Certain personality‐BMI associations were moderated by sample properties, such as proportions of women or participants with obesity; these moderation effects were replicated in the individual‐level analysis. Finally, facet‐based personality "risk" scores accounted for 2.3% of variance in BMI in a separate sample of individuals (N = 3569), 409% more than domain‐based scores. Taken together, personality‐BMI associations are facet specific, and delineating them may help to explain obesity‐related behaviours and inform intervention designs. Preprint and data are available athttps://psyarxiv.com/z35vn/ .